Immune Related Adverse Events of the Thyroid – A Narrative Review - Muir, Christopher A.; Tsang, Venessa H. M.; Menzies, Alexander M.; Clifton-Bligh, Roderick J. (Frontiers in Endocrinology, 2022)
Immune checkpoints are small molecules present on the cell surface of T-lymphocytes. They maintain self-tolerance and regulate the amplitude and duration of T-cell responses. Antagonism of immune checkpoints with monoclonal antibodies (immune checkpoint inhibitors) is a rapidly evolving field of anti-cancer immunotherapy and has become standard of care in management of many cancer subtypes. Immune checkpoint inhibition is an effective cancer treatment but can precipitate immune related adverse events (irAEs). Thyroid dysfunction is the most common endocrine irAE and can occur in up to 40% of treated patients. Both thyrotoxicosis and hypothyroidism occur. The clinical presentation and demographic associations of thyrotoxicosis compared to hypothyroidism suggest unique entities with different etiologies. Thyroid irAEs, particularly overt thyrotoxicosis, are associated with increased immune toxicity in other organ systems, but also with longer progression-free and overall survival. Polygenic risk scores using susceptibility loci associated with autoimmune thyroiditis predict development of checkpoint inhibitor associated irAEs, suggesting potentially shared mechanisms underpinning their development. Our review will provide an up-to-date summary of knowledge in the field of thyroid irAEs. Major focus will be directed toward pathogenesis (including genetic factors shared with autoimmune thyroid disease), demographic associations, clinical presentation and course, treatment, and the relationship with cancer outcomes.